Geographic inequality in funding by National Institutes of Health negatively impacts almost one-half of the states in the United States - Caulder, Elizabeth; Zhang, Jiajia; Nagarkatti, Mitzi; Nagarkatti, Prakash (Frontiers in Public Health, 2024)
NIH is the primary federal agency in the United States that supports biomedical research, training, and clinical trials. In 1993, authorized by Congress, NIH initiated a funding program called Institutional Development Award (IDeA) to support states, called IDeA states, which received low levels of NIH funding. In the current study, we analyzed data on various NIH funding mechanisms awarded to 23 IDeA vs 27 non-IDeA states, as identified by NIH. We compared these data to the population size, federal taxes paid, and the number of PhDs and Post-doctoral Fellows trained in IDeA vs non-IDeA states. The non-IDeA states received 93.6% of the total NIH funding, whereas IDeA states received only 6.4%. On average, one Institutional Training Grant was received for every 24 PhDs trained in non-IDeA states, while IDeA states received one such grant for every 46 PhDs. The non-IDeA states comprised 84.3% of the US population, whereas IDeA states comprised 15.7%. Thus, on a per capita basis, non-IDeA states received 120 from NIH, whereas IDeA states received 45. For every million dollars contributed by the non-IDeA states toward federal taxes, they received 7903 in NIH funding, while the IDeA States received 4617. For FY 2022, the NIH funding created an economic activity of 90.6 billion in non-IDeA states and only 6.3 billion in IDeA states. When total NIH funding was analyzed for 1992, 2002, 2012, and 2022, IDeA states received 4.7% of the total NIH funding in 1992, 7.2% in 2002, 6.8% in 2012 and 6.5% in 2022. Thus, IDeA states' share of NIH funding remained relatively unchanged for the past 20 years. Eliminating the geographic disparity in NIH funding is crucial for achieving equitable health outcomes across the US, and for the IDeA states to successfully train future generations of physicians and scientists, as well as grow the regional economy. Although the NIH IDeA programs have helped enhance the research capacity in IDeA states, the IDeA funding currently constitutes less than 1% of the total NIH budget. Thus, it is critical to increase NIH funding to IDeA states to improve health outcomes for all Americans.